Post-COVID-19 pandemic: Examining the moderating role of event image on visitors’ intention to revisit major events - Lo, May Chiun; Mohamad, Abang Azlan; Thong, Jun Zhou; Law, Fung Yee (Turyzm/Tourism, 2025)
Grasping the perspectives of consumers is a fundamental focus for those managing events and festivals. This study investigated the impacts of aspects of awareness and event experience, namely perceived value, service quality and event image on satisfaction, along with revisit intentions to major events. The study used a quantitative analysis based on 1265 valid responses collected from a survey conducted during several major events that were held in Sarawak, Malaysia. Via partial least squares-structural equation modelling (PLS-SEM), the findings revealed service quality as a crucial motivator towards the attendees’ satisfaction levels, and this led to their revisit intentions. The event image was found to enhance the association, while the impacts of awareness and perceived value on satisfaction were not significant. The study provides event organizers with valuable insights regarding attendees’ perceived aspects of an event, enabling the effective planning and implementation of future major events post-COVID-19.